Gb/s Real-Time Visible Light Communication System Based on White LEDs Using T-Bridge Cascaded Pre-Equalization Circuit - Haiqi Zhang; Aiying Yang; Lihui Feng; Peng Guo (IEEE Photonics Journal)
We demonstrate a Gb/s real-time visible light communication (VLC) system based on NRZ-OOK by a phosphorescent white light-emitting diode (LED). We propose an equalizer employed by an RC series-parallel connection cascade circuit based on the T-bridge structure. With the proposed circuit, the 3-dB bandwidth of the VLC system can be extended from 1 to 520 MHz. The Bit Error Ratio (BER) of the system was $7.36 × 10^{-4}$ , and the data rate was 1 Gb/s at a distance of 1.5 m. To the best of our knowledge, this is the highest real-time data rate and 3-dB bandwidth achieved based on a white LED.